Efek Penambahan Serat Polypropylene terhadap Kuat Tarik Belah Beton Ringan - Sultan, Mufti Amir; Hi Bayan, Ilman Nafiyanto A; Gaus, Abdul; Saputra, Muhammad Taufik Yuda; Irnawaty, Irnawaty (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2025)
Lightweight concrete is concrete weighing less than 1840 kg/m³. Lightweight concrete tends to have a low tensile strength, and due to the characteristics of the lightweight aggregate used, in planning the concrete mixture, fiber is added to increase the tensile strength of the lightweight concrete itself.  This study analyzes the effect of adding polypropylene fiber to lightweight concrete mixtures with volume levels of 0.1 kg/m³, 0.3 kg/m³, 0.5 kg/m³ and 0.7 kg/m³. The number of 15x30 cm cylindrical specimens was 15 pieces for the split tensile strength test. The test uses a compression tester, where the cylindrical specimen is placed horizontally and then loaded to the maximum acceptable load. The results showed that adding polypropylene fiber to lightweight concrete increased the split tensile strength along with the addition of various polypropylene fibers up to 0.5 kg/m³. After exceeding 0.5 kg/m³, the split tensile strength decreased. The maximum split tensile strength value is 21.64 kg/cm2 at a 0.5 kg/m³ volume polypropylene fiber. The workability of fiber concrete tends to decrease with the addition of polypropylene fiber into the lightweight concrete mixture. The maximum volume weight produced is 1471 kg/m3, categorized as lightweight concrete.